Efficacy of Buccal Infiltration Combined with Inferior Alveolar Nerve Block versus Inferior Alveolar Nerve Block Alone in Mandibular Molars with Irreversible Pulpitis: A Randomized Clinical Trial. - Gul, Madiha; Abu Bakar Sheikh; Shahid Islam; Azam Muhammad Aliuddin; Nina Ayaz; Rabia Aslam (International Journal of Endorsing Health Science Research, 2025)
Background: To evaluate the comparative efficacy of the inferior alveolar nerve block (IANB) alone and in combination with buccal infiltration for achieving effective pulpal anesthesia and postoperative pain reduction in mandibular molars diagnosed with irreversible pulpitis. Methodology: A randomized, parallel-group, open-label clinical trial was conducted in the Endodontics Department of Fatima Jinnah Dental College Hospital, Karachi, from October 2023 to May 2024. A total of 150 patients diagnosed with irreversible pulpitis in mandibular molars were randomly assigned into two groups. Group I received 1.8 mL of 2% lidocaine with 1:100,000 epinephrine via IANB, while Group II received 1.5 mL via IANB supplemented with 0.3 mL buccal infiltration. Pain was evaluated using a Visual Analog Scale (VAS) before anesthesia, 15 minutes post-injection, during access cavity preparation, immediately after treatment, and after 12 hours. Data were analyzed using repeated-measures ANOVA with a significance level of p ≤ 0.05. Results: Both groups demonstrated similar pre-operative VAS scores (p > 0.05). However, Group II showed significantly lower pain scores after 15 minutes and during cavity preparation compared to Group I (p < 0.001). Postoperative and 12-hour follow-up pain scores were comparable between groups (p > 0.05). No adverse effects were observed. Conclusion: Supplemental buccal infiltration combined with IANB provides significantly better intraoperative pulpal anesthesia compared to IANB alone in mandibular molars with irreversible pulpitis. However, its effect on prolonged postoperative pain relief remains minimal.